Outcomes of segmentectomy versus lobectomy in adults with non-cystic fibrosis bronchiectasis - José de Sá Moraes Neto; Isabele Alves Chirichela; Alessandro Wasum Mariani; Ricardo Mingarini Terra; Paulo Manuel Pêgo Fernandes (Jornal Brasileiro de Pneumologia)
ABSTRACT Objective: Surgical resection remains the gold standard treatment for bronchiectasis in patients who present with hemoptysis or suppuration, as well as in those who do not respond to clinical treatment. We sought to investigate the efficacy of sublobar resection (segmentectomy) and compare it with that of lobar resection (lobectomy) in patients with non-cystic fibrosis bronchiectasis. Methods: Patients undergoing lobectomy or segmentectomy between 2019 and 2023 were included in the study. We analyzed intraoperative complications and postoperative outcomes, including length of hospital stay, length of ICU stay, and disease recurrence. Results: There was no significant difference between the lobectomy and segmentectomy groups regarding the occurrence of intraoperative complications such as bleeding > 1000 ml, cardiogenic shock, and ventilatory instability (p > 0.999). However, the frequency of complications was significantly lower in the segmentectomy group than in the lobectomy group (p = 0.016). Hospital stays were longer in the lobectomy group than in the segmentectomy group (16 days vs. 5 days; p = 0.027), as were ICU stays (7 days vs. 1 day; p = 0.006). There was no significant difference between the lobectomy and segmentectomy groups regarding the recurrence rate (p = 0.541). Conclusions: Early identification of bronchiectasis patients who are candidates for surgical resection is essential because those who are identified as such early on are candidates for parenchyma-sparing resections, which are similar to lobar resections in terms of disease control and lead to shorter hospital stays and better postoperative outcomes.